Model Konseling Rational Emotive Behavior Therapy (REBT) Dalam Menanggulangi Kenakalan Remaja - Husni Ismail; Muhammad Amin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescence is a period of self-discovery, when faced with contradictory and unstable environmental conditions. So this will make teenagers trapped in uncertainty, so they do not realize that the actions they take are contrary to the rules of values ​​and norms in people's lives. This if left unchecked will interfere with many things including his own development. This study aims to determine how the emotional rational counseling model in tackling juvenile delinquency. This effort is considered capable of making teenagers to think rationally and think healthy. This study uses a literature review research method with data sources from previous books and articles. Based on the results of this study indicate that the rational emotive counseling model in overcoming juvenile delinquency is one of the guidance and counseling service strategies to reduce juvenile delinquency. Rational counseling is more focused on educative efforts, counselors must actively teach clients (problem teenagers) to change their irrational ideas, attitudes and behavior to rational, positive and realistic situations, and be carried out comprehensively by changing cognitive, emotive aspects. and behavioristic.